A STUDY ON COLLAGE TECHNIQUE BY CONTEMPORARY INDIAN ARTISTS - Verma, Manisha; Gupta, Ishwar Chand (ShodhKosh: Journal of Visual and Performing Arts, 2022)
In Indian Culture the Inclusion of Various arts and thoughts such a powerful Medium in which human being can express their feelings, thoughts in a cogent manner through paint brush because we believed that contemporary art means today from the art of. Though the in caption of collage technique had been come into innovation since 1912-14 by artist George Braque and Pablo Picasso. Collage technique is a visual depiction of feelings views hovering in mind made from conjoining different forms, materials like news-paper clipping, ribbons, bits of colored or handmade paper's portions of other artwork, photographs and such glued to a base surface. The technique of collage is very suitable to present a particulars atmosphere or context that you want to capture in the form of new product ideas and concepts. Visual thinking and visualization of ideas is inherent in thinking up ideas and solution in design some issue cannot simplify be captured in words and this is where collages assist in structuring, developing, analyzing, and presenting (depicting) the visual issues that are difficult to express in words. Collage technique tool has given opportunities by depicting their prumaeval expression using fast/bright colour and created using fast/bright colours and created attractive pictures enchanting with Indian culture fragrance by contemporary Indian artist. The rising contemporary Indians artist stirring towards blossoming and spreading sustainable fragrance on collage technique.